Analysis of the generation and redistribution of income in Mexico through a social accounting matrix - Aguayo Téllez, Ernesto; Chapa Cantú, Joana C.; Ramírez Grimaldo, Nelly C.; Rangel González, Erick (Estudios Económicos de El Colegio de México, 2009)
We construct a social accounting matrix for the Mexican economy of the year 2004. In addition to the high level of disaggregation, the main contribution of this matrix is the use of microdata from the ENIGH 2004 to form an income-expenditure structure of the households account. As an application, this paper formulates the accounting multipliers model that allows us to analyze the generation and redistribution of income in Mexico, as well as to determine the induced and redistributed effects of a unitary exogenous injection of income, such as international remittances.